846 Towards an evidence-based zero vision on residential fires. (1st September 2016) - Andersson, Ragnar; Nilsen, Per
Abstract : Background: Sweden has a national zero vision on fire. Nobody should be killed or seriously injured from fires. Despite this, some 100 people are killed annually with most victims being of poor health, elderly or disabled. A multi-centre research program from 2014 to 2017 involving more than ten researchers, aims to investigate why these groups are at excessive risk of dying or getting seriously injured in residential fires, and to explore further preventative possibilities with regard to these vulnerable groups. Methods: The program consists of seven sub-projects, derived from a tentative generic model of the residential fire process. Quantitative and qualitative approaches are applied. Results: By 1 st of November 2015 the project has yielded five international publications: Jonsson A et al., Assessing the number of fire fatalities in a defined population (Accepted with minor rev., Journal of safety research) Jonsson A et al, Fire-related mortality in Sweden – temporal trends 1952 – 2013 (Accepted with minor rev., Fire Technology) Nilson, F et al., Differences in determinants amongst individuals reporting residential fires in Sweden – results from a cross-sectional study (Fire Technology, 2015) Bonander C et al., Investigating the effect of banning non-reduced ignition propensity cigarettes on fatal residential fires in Sweden. (Accepted, European Journal of Public Health) Jaldell H et al., How important is the time factor? Saving lives using fire and rescue services. (Submitted to Fire Technology, August 2015) Conclusions: In line with zero vision philosophies in parallel policy fields, such as traffic safety, merely preventing accidents (crashes or fires) and rescuing victims appear insufficient strategies for protecting human life from residential fires.